Management of the Surabaya Syariah Namira Hotel in the Perspective of Sharia Hotel Principles and Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 2 of 2014 - Ubaid Aisyul Hana (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
This research is a field research to highlight service of the Surabaya Syariah Namira Hotel in the perspective of sharia hotel principles and Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 2 of 2014. To elaborate on that theme, there are two core issues that will be answered, namely: how is the management of the Surabaya Syariah Namira Hotel? And how is the management of the Surabaya Syariah Namira Hotel in the perspective of Sharia principles and the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 2 of 2014? The data obtained through observation, interview and documentation. The results showed that the service and management of the Surabaya Syariah Namira Hotel is carried out in accordance with the internal hotel regulations and completed with facilities as required in sharia hotel. While based on sharia principles and the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 2 of 2014, the Surabaya Syariah Namira Hotel is adequate to be classified as sharia hotel and as the Hilāl-1 category.